2002
DOI: 10.1006/cbir.2002.0926
|View full text |Cite
|
Sign up to set email alerts
|

VASCULAR ENDOTHELIAL GROWTH FACTOR INDUCES PROTEIN KINASE C (PKC)‐DEPENDENT Akt/PKB ACTIVATION AND PHOSPHATIDYLINOSITOL 3′‐KINASE‐MEDIATED PKCδ PHOSPHORYLATION: ROLE OF PKC IN ANGIOGENESIS

Abstract: Activation of the protein kinase Akt/PKB mediates VEGF‐dependent endothelial cell survival and eNOS activation. Here we examined the role of PKC in mediating VEGF‐induced Akt activation. The PKC inhibitors GF109203X and calphostin C inhibited VEGF‐induced Akt activation. Rottlerin and Go6976, inhibitors with specificities for PKCδ and α, respectively, also strongly inhibited VEGF‐induced Akt activation. VEGF‐induced Akt activation was prevented by down‐regulation of PKC induced by prolonged pretreatment with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…[12] Bisindolylmaleimide I reduced HUVEC vasculogenesis by about half at concentrations above 1 μm, also consistent with earlier reports. [60,61] For HRMVECs, the compound showed no clear inhibition of the endothelial network as previously reported. [12] Plerixafor had a similar effect on both cell types.…”
Section: High-throughput 3d Vasculogenesis Models Enable Direct Compa...supporting
confidence: 72%
“…[12] Bisindolylmaleimide I reduced HUVEC vasculogenesis by about half at concentrations above 1 μm, also consistent with earlier reports. [60,61] For HRMVECs, the compound showed no clear inhibition of the endothelial network as previously reported. [12] Plerixafor had a similar effect on both cell types.…”
Section: High-throughput 3d Vasculogenesis Models Enable Direct Compa...supporting
confidence: 72%
“…In the case of PKCa, this residue is Thr 497 [Bornancin and Parker, 1996], while for PKCe, it is Thr 566 [Le Good et al, 1998]. PDK-1 also phosphorylates Thr 505 of PKCd, and Thr 410 of PKCz [Chou et al, 1998;Gliki et al, 2002]. This first phosphorylation step triggers autophosphorylation at two other sites in the catalytic domain, the first in the ''turn motif,'' and the last in the ''hydrophobic motif '' [Dutil et al, 1998].…”
mentioning
confidence: 99%
“…In this sense, signaling through phosphatidylinositol-3-kinase (PI3K) and its downstream kinase Akt has been widely implicated in cell survival [29], therefore the relationship between PKC activation and Akt function has been subject of intense investigation. Some studies have shown that PKCs activate Akt in endothelial and myeloid cells, an effect that has been attributed in most cases to the classical PKC isoforms [30,31]. Nevertheless, it was also shown that in normal mammary cells PKC overexpression conferred resistance against cytotoxic drugs throughout a substantial elevation in the levels of activated Akt [25].…”
Section: Pkc Downstream Signaling Pathwaysmentioning
confidence: 99%